Whale song - Johnston, Tony, 1942-; Young, Ed (New York : Putnam, 1987)
Counting as they sing, whales use their mighty voices to pass on to one another the numbers from one to ten.
School Library Journal.
Book Links (A.L.A.).
School Library Media Quarterly (A.A.A.L.).
4.9
K-3
Keywords: Whales -- Fiction; Counting; Whales -- Fiction; Counting; Whales -- Fiction; Counting